2022
DOI: 10.1111/jonm.13757
|View full text |Cite
|
Sign up to set email alerts
|

Virtue ethics in health care teams; its time has come: Review of the nursing virtue ethics literature

Abstract: Aim To summarize and evaluate the nursing virtue ethics literature, examine how virtue ethics has been applied to health care teams, offer a new framework to guide understanding and development of virtuous health care teams and offer recommendations to nurse leaders. Background With the unprecedented levels of incivility and turnover in the post‐COVID‐19 world, virtue ethics may provide an innovative approach for nursing leaders working to rebuild healthy practice environments. Evaluation An integrative review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Other healthcare professions have recognised the utility of VE in both practice and education with multiple papers arguing for its utility. 16,17,[30][31][32] However, there is a paucity of empirical evidence to demonstrate the uptake of this approach, although the few studies which have attempted to do so have shown some promising results. [33][34][35][36] This lack of evidence, however, should not be a reason to avoid pushing this approach forward.…”
Section: Gap In Current Practicementioning
confidence: 99%
“…Other healthcare professions have recognised the utility of VE in both practice and education with multiple papers arguing for its utility. 16,17,[30][31][32] However, there is a paucity of empirical evidence to demonstrate the uptake of this approach, although the few studies which have attempted to do so have shown some promising results. [33][34][35][36] This lack of evidence, however, should not be a reason to avoid pushing this approach forward.…”
Section: Gap In Current Practicementioning
confidence: 99%
“…For example, nursing unit managers or servant leaders who prioritised their followers’ needs above their own amplified positive behaviours and interactions, whereas unit-level virtuous climates were negatively associated with unit-level incivility 15. One recent review, however, concluded that there was a dearth of research on virtue ethics and nursing 16. Incivility is a potent threat to professionalism.…”
Section: Introductionmentioning
confidence: 99%
“… 15 One recent review, however, concluded that there was a dearth of research on virtue ethics and nursing. 16 Incivility is a potent threat to professionalism. As such, incivility is an unacceptable practice in medicine, and therefore, should be prevented.…”
Section: Introductionmentioning
confidence: 99%